Takatāpui/LGBTIQ+ People’s Experiences of Homelessness and Sex Work in Aotearoa New Zealand - Brodie Fraser; Elinor Chisholm; Nevil Pierse (Anti-Trafficking Review, 2023)
At present, there is limited research on the intersection of sex work, takatāpui/LGBTIQ+ communities, and experiences of homelessness in Aotearoa New Zealand. This paper helps to bridge this gap, exploring how takatāpui/LGBTIQ+ people who had been failed by the welfare state engaged in sex work during periods of homelessness, and expressed agency in difficult circumstances. Specifically, we look at sex and sex work as a means to secure basic needs, and in the context of exploitative relationships; the emotional effects of sex work; and safety and policing. A stronger welfare state is needed to provide sufficient support for people to realise an adequate standard of living and treat them with dignity and respect.